Global climate change and its effects on human habitat and environment in Malaysia - Haliza Abdul Rahman (Environmental Management Society, Malaysia, 2009)
Climate change is the biggest threat to nature and humanity in the 21st century. Climate change means annual temperature of the earth has swung up and down by several degrees Celsius over the past million years. Temperature records in the past 30 to 50 years have shown warming trends in most places including Malaysia. Climate change may bring about an increase in the frequency and intensity of extreme weather events, such as, droughts, storms and floods. The effects of global climate change are many and varied. Climate change is caused by the emission of heat-trapping gases – mostly carbon dioxide (CO2) – from vehicles, industry, power plants and deforestation. As these gases build up, they act like a thick blanket, overheating the planet, changing our climate, and threatening our health, economy and natural environment. An analysis of temperature records in Malaysia shows a warming trend. For Malaysia, the temperature changes range from +0.70C to +2.60C, while precipitation changes range from -30% to +30%. Climate change in Malaysia showed this phenomenon have negative impacts on human habitats such as agriculture, forests, water resources, coastal resources, health and energy sector